Different Quenching Media Effect on Microstructure, Hardness,and Corrosion of Medium Carbon Steel - Syaripuddin; Sopiyan; Syamsuir; Tegar Firman Pamungkas; Ahmad Lubi; Ferry Budhi Susetyo (Fakultas Teknik Universitas Pancasila, 2025)
Medium carbon steel is widely used due to could conduct heat treatment to modify the microstructure and mechanical properties. Quenching is one method to modify the microstructure and mechanical properties. In the present study conducted heating samples at 850°C using an electric furnace, then held them for 60 minutes and quenched in various media (saline water, oil, and distilled water). Afterward, the quenched sample was investigatedmicrostructure, hardness, and corrosion using an optical microscope, Vickers hardness tester, and weight loss method. 5% NaCl quenching media could result in samples more uniform and martensite due to the high cooling rate.More uniforms and martensite have the beneficial highest hardness and lowest corrosion rate for around 762.4 HV and 76.04 mpy.